1990
DOI: 10.1016/0883-2927(90)90016-x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of formation waters, Alberta Basin, Western Canada sedimentary Basin. I. Chemistry

Abstract: Inorganic chemical analyses and short-chain aliphatic acid content are used to interpret the origin and compositional evolution of formation waters in the Alberta portion of the Western Canada Sedimentary Basin. Forty-three formation water samples were obtained covering a stratigraphic interval from Devonian to Cretaceous. The data show that: (1) there is a subaerially evaporated brine component that shows no apparent contribution of waters derived from evaporite dissolution; and (2) formation waters have main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(54 citation statements)
references
References 51 publications
1
53
0
Order By: Relevance
“…As with high-temperature boiling, evaporation of surface waters leads to the loss of water vapour and consequent isotopic fractionation (Viglino et al, 1985). Large shifts in the original H-and O-isotopic composition of the fluids can occur, to higher 6D and 6~SO values (Knauth and Beeunas, 1986), and Connolly et al (1990) have recently suggested that combined mixing-evaporation processes can lead to large variations in the 6D contents of formation waters. Deep sedimentary basins containing thick accumulations of Permo-Triassic Red Beds and evaporite horizons are present adjacent to the Cornubian Massif (Smith, in press) and, therefore, could have produced such fluids.…”
Section: Resultsmentioning
confidence: 99%
“…As with high-temperature boiling, evaporation of surface waters leads to the loss of water vapour and consequent isotopic fractionation (Viglino et al, 1985). Large shifts in the original H-and O-isotopic composition of the fluids can occur, to higher 6D and 6~SO values (Knauth and Beeunas, 1986), and Connolly et al (1990) have recently suggested that combined mixing-evaporation processes can lead to large variations in the 6D contents of formation waters. Deep sedimentary basins containing thick accumulations of Permo-Triassic Red Beds and evaporite horizons are present adjacent to the Cornubian Massif (Smith, in press) and, therefore, could have produced such fluids.…”
Section: Resultsmentioning
confidence: 99%
“…Brines from Ordovician age and younger strata in the Illinois Basin (i.e., Stueber et al, 1987Stueber et al, , 1993Walter et al, 1990;Walter, 1991, 1994) and brines from Michigan, southwest Arkansas, eastern Ohio, the Alberta Basin and Canadian Shield Lowry et al, 1988;Connolly et al, 1990;Wilson and Long, 1993a,b) have been studied extensively. These studies used various geochemical techniques such as ion concentration ratios, 87 Sr/ 86 Sr, d 18 O, and dD values to understand groundwater evolution including mixing scenarios with evaporitic brines, glacial and non-glacial meteoric waters, signatures of original seawater, the influences of subaerial exposure and evaporation, and water-rock interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Individual lines: (1) Canadian Shield (Precambrian) fromFrape et al (1984);(2)and(3)Michigan Basin brines (Paleozoic) fromWilson and Long (1993a,b); (4) southwest Arkansas basin (Mesozoic) fromMoldovanyi and Walter (1992); (5) the BFL global regression [Ca excess = 0.967(Na deficit) + 140.3; R = 0.981] fromDavisson and Criss (1996); (6) eastern Ohio basin (Paleozoic) fromLowry et al (1988); and (7) Alberta Basin of Canada (Paleozoic and Mesozoic) fromConnolly et al (1990).…”
mentioning
confidence: 99%
“…4). CLE is within range of formation waters from the Devonian of west-central Alberta (Connolly et al, 1990;Michael et al, 2003), which these authors interpreted to represent highly evaporated seawater that was variably diluted by meteoric water following the Laramide Orogeny.…”
Section: Br / CL Datamentioning
confidence: 96%